Language Proficiency Tests in Malayalam - Syamala Kumari, B. (Central Institute of Indian Languages Mysore, 1984)
This book is a Language Proficiency Tests in Malayalam with an objective measure to assess one's knowledge of Malayalam both as first language and as a second language.
Keywords: Malayalam; Language Proficiency Tests in Malayalam; Language Proficiency; Malayalam; Malayalam